Growing kalo (taro) to promote culture and health in the Continental US - Ka’ula, Leialoha; Ellison, Nicole lee Kamakahiolani; James, Constance; Oshiro, Ashley; Ideue, Kacyn; Ka’ula, Kahoku; Jackson, Alexandra Malia (Frontiers in Public Health, 2025)
IntroductionA growing number of Native Hawaiians live in the continental US. Without access to the ‘āina (land) in Hawai’i, māla kalo (community gardens used to grow taro) may offer a space for these communities to increase access to traditional foods and create community connections.MethodsWe formed a community–research hui to engage in a community-based participatory research process to explore potential benefits of a māla kalo. We used an explanatory mixed-methods Indigenous evaluation approach, including a survey and interview with program volunteers and leaders to identify implementation strategies and thematic analysis to explore potential benefits of a māla kalo on the continent.ResultsA total of 12 participants and 5 program leaders, aged 18 to 75 years, completed a survey and interview at the end of the 2023 growing season. The findings suggested high levels of satisfaction and an interest in participating more frequently. Qualitative data suggested that volunteering at the māla kalo may support connections to self, community, and land, learning and sharing of knowledge, and connection to culture.ConclusionCommunity gardens that grow traditional foods may foster relationships, health, and culture within a displaced Indigenous community. Future steps should include continued evaluation of the health benefits of community gardens that grow traditional foods using culturally relevant measures and infrastructure development to create resources that support other organizations in scaling up similar programs.